2021
DOI: 10.1007/s00170-021-07743-7
|View full text |Cite
|
Sign up to set email alerts
|

Formation of metal composites by detonation spray of powder mixtures

Abstract: The feasibility study of elaboration of metal composite coatings by detonation spray using the blends of iron, nickel, copper, cobalt, and aluminum powders was performed using different spray modes. The numerical simulation of particle parameters showed that the particles formed the coating in solid, semi-molten, or molten state depending on the spraying modes, particle material, and particle size. It was shown that successful formation of the coating containing all powder mixture components could be achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…As a result, a fraction of the iron particles could cool down in the gas jet after the barrel exit and impact the substrate in the solid state. A similar conclusion was drawn in our previous work [11].…”
Section: As-sprayed Precursor Composite Coatingssupporting
confidence: 93%
See 4 more Smart Citations
“…As a result, a fraction of the iron particles could cool down in the gas jet after the barrel exit and impact the substrate in the solid state. A similar conclusion was drawn in our previous work [11].…”
Section: As-sprayed Precursor Composite Coatingssupporting
confidence: 93%
“…In our previous work, it was shown that the highest coating density and the highest powder deposition efficiency are achieved when spraying of the mixtures is performed in the "hot" spraying mode [11]. In this mode, the particle temperature is higher than the melting point of the metals contained in the mixture [11]. In the present work, the experiments were also performed in the "hot" mode.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations